1970
DOI: 10.1111/j.1471-4159.1970.tb00544.x
|View full text |Cite
|
Sign up to set email alerts
|

GLYCOPROTEINS OF SUBMAXILLARY SALIVA OF THE CAT: DIFFERENCES IN COMPOSITION PRODUCED BY SYMPATHETIC AND PARASYMPATHETIC NERVE STIMULATION1

Abstract: Abstract— Saliva samples were obtained from the cannulated submaxillary ducts of the cat during stimulation of the peripheral cut end(s) of (1) the cervical sympathetic nerve, (2) the chordalingual (parasympathetic) nerve and (3) both nerves at the same time. In nine experiments the ratios of neuraminic acid to fucose and to hexosamine were consistently 2·5–4 times higher in saliva evoked by sympathetic nerve stimulation than in that produced by parasympathetic stimulation. This was not attributable to differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

1972
1972
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…In addition, biochemical analyses of saliva from cat submandibular glands has shown different types of protein in sympathetic and parasympathetic salivas (see Dische et al, 1970;Kahn et al, 1969;Komarov and Stavraky, 1940). These studies, however, gave no information about the cellular origins of the different protein constituents secreted into the saliva.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, biochemical analyses of saliva from cat submandibular glands has shown different types of protein in sympathetic and parasympathetic salivas (see Dische et al, 1970;Kahn et al, 1969;Komarov and Stavraky, 1940). These studies, however, gave no information about the cellular origins of the different protein constituents secreted into the saliva.…”
Section: Introductionmentioning
confidence: 99%
“…Those studies only examined saliva induced by a parasympathetic secretagogue, despite the fact that salivary secretions are also elicited by activity of the sympathetic nervous system. Such adrenergic secretions differ from cholinergic saliva in both protein concentration and composition (7,8).…”
Section: Introductionmentioning
confidence: 99%
“…Those studies only examined saliva induced by a parasympathetic secretagogue, despite the fact that salivary secretions are also elicited by activity of the sympathetic nervous system. Such adrenergic secretions differ from cholinergic saliva in both protein concentration and composition (7,8).Several lines of evidence suggest that NGF might be secreted from the submaxillary gland after adrenergic stimulation. This growth factor is concentrated in the convoluted granular tubules (9, 10) with a number of other proteins that are secreted by the gland: (i) renin (or isorenin) (11, 12), (ii) esteroproteases (13; 14), and (iii) epidermal growth factor (EGF) (15,16 In the present paper and in an earlier abstract (18), we report exceedingly high NGF concentrations in salivary secretions elicited by epinephrine or norepinephrine, but not by isoproterenol or pilocarpine.…”
mentioning
confidence: 99%
“…An area of future research in cat-related DVT is the potential presence of thrombus-inducing proteins in the feline saliva. It is widely known that some animals have toxins that disrupt hemostasis [18] and there is some experimental evidence that cat saliva composition can change with different states of sympathetic and parasympathetic stimulation [19]. Our knowledge of the differences between mammalian saliva is still limited, but recent advances have shown that there are many species-specific proteins with unclear functions [20] that, if properly characterized, can shine some light on our understanding of exogenous thrombotics.…”
Section: Discussionmentioning
confidence: 99%